2013
DOI: 10.1111/roiw.12041
|View full text |Cite
|
Sign up to set email alerts
|

Does Contracting Make Farmers Happy? Evidence from Senegal

Abstract: In this paper we use a subjective well‐being approach to evaluate the welfare impact of contract‐farming. We analyze the impact of contract‐farming on self‐reported happiness using original panel data from a farm‐household survey in the Niayes region in Senegal. We use different econometric techniques and show that, when correcting for time invariant unobserved heterogeneity, contract‐farming has a positive effect on subjective well‐being. We find diverging effects for different types of contracts, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 64 publications
2
56
0
Order By: Relevance
“…Export or processing companies often source agricultural products through outgrower schemes, in order to ensure consistent and high-quality supply (Barrett et al, 2012;Dedehouanou et al, 2013;Bellemare and Novak, 2016). Also in domestic supply chains in developing countries, the role of contracting increases.…”
Section: Introductionmentioning
confidence: 99%
“…Export or processing companies often source agricultural products through outgrower schemes, in order to ensure consistent and high-quality supply (Barrett et al, 2012;Dedehouanou et al, 2013;Bellemare and Novak, 2016). Also in domestic supply chains in developing countries, the role of contracting increases.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no study was identified that collected data before and after a firm offered contractual arrangements to smallscale farmers. A study by Dedehouanou, Swinnen and Maertens (2013), which did not quantitatively estimate income effects, collected data at two points in time, but some farmers were already participating in contract farming during the first wave of data collection.…”
Section: Types Of Study Designmentioning
confidence: 99%
“…Four more studies were excluded for having a unique outcome variable, making it impossible to include in the meta-analysis for lack of a relevant comparison group. These studies measured the effect of contract farming on happiness (Dedehouanou et al, 2013), growth rates (Herck et al, 2012), assets (Michelson, 2013), and marketed surplus (Tadesse and Guttormsen 2009). Another study was excluded for providing so little information that it was impossible to understand and interpret the tables and figures (Munungo, 2012).…”
Section: Excluded Studiesmentioning
confidence: 99%
“…One strand of the literature focuses on low-income countries and finds positive impacts of the inclusion of farmers in export supply chains on happiness [15], on primary school enrolment [16] and on food security [17]. Regarding the creation of employment opportunities, Van den Broeck and Maertens [18] find that female labor market participation reduces fertility rates.…”
Section: Introductionmentioning
confidence: 99%